A Critical Analysis of Judicial Appointment Process and Tenure of Constitutional Justice in Indonesia - Faiz, Pan Mohamad (Hasanuddin University, 2016)
The judicial appointment process is one of essential elements for maintaining judicial independence and public confidence of a court. This article analyses the practices of judicial appointment process exercised by three different main state institutions in selecting constitutional justice in Indonesia where the mechanism and process for selecting them have been implemented differently. It also examines the tenure of constitutional justice, which is a five-year term and can be renewed for one term only, that may lead to another problem concerning the reselection process of incumbent constitutional justices for their second term. The article concludes that the judicial appointment process and tenure of constitutional justice in Indonesia have to be improved. It suggests that if the proposing state institutions could not meet the principles of transparency, participation, objective and accountable required by the Constitutional Court Law, the judicial appointment process should be conducted by creating an independent Selection Committee or establishing a cooperation with the Judicial Commission. Additionally, the tenure of constitutional justices should also be revised for a unrenewable term with a longer period of nine or twelve years.